Selective transformations of 2-(p-toluenesulfonyl)-N-tosylhydrazones to substituted 1, 2, 3-thiadiazoles. (8th January 2021) - Feng, Yijiao; He, Jing; Li, Weiwei; Yang, Zhen; Wei, Yueting; Liu, Ping; Zhao, Jixing; Gu, Chengzhi; Wang, Wenli
Abstract: Selective transformations of 2-( p -toluenesulfonyl)- N -tosylhydrazones with different sulfur sources have been established. A series of 4-aryl-1, 2, 3-thiadiazoles and novel 4-aryl-5-tosyl-1, 2, 3-thiadiazoles were selectively constructed by the adjustment of reaction conditions. These protocols feature short reaction time, good compatibility of functional group, easily available materials, and good selectivity. Graphical abstract: Image 1 Highlights: Reactions of 2-( p -toluenesulfonyl)- N -tosylhydrazones with different sulfur sources have been established. A series of 4-aryl-1, 2, 3-thiadiazoles and novel 4-aryl-5-tosyl-1, 2, 3-thiadiazoles were selectively constructed by the adjustment of reaction conditions. These protocols feature short reaction time and good selectivity.